Penggunaan Metode Al-Husna Untuk Peningkatan Kualitas Membaca Al-Qur'an Dalam Program Pengenalan Al-Qur'an Di SMP Muhammadiyah 8 Surakarta Tahun Ajaran 2016-2017 - Oktavia Esperanza Hartono, Syifa, Dra. Chusniatun, M.Ag (2017)
As moslems, we have the obligation to learn the holy Qur'ān. The most basic term in learning the holy Qur'ān is an ability to read the Qur'ān. Learning how to read the Qur'ān is n t t diffi ult, if they arediligent and struggle in memorizing the letters of Hijaiyyah starting from separate letters to connected letters. However, if students have low desire and motivation there will be problems causing the students hard to read the holy Qur'ān fluently, fitting to the Tajwid rules. Since the last few years, a lot of practical methods to read the holy Qur'ān have been implemented in formal and non-formal schools. In order to apply the methods as well, there will be needed teachers who can teach, support, motivate, supervise and control the students continuously, then students can read the holy Qur'ān fluently. The problem studied in the research is: How is the using of Al-Husna method to increase the quality in reading the holy Qur'ān Recognizing Al- Qur'ān Program of SMP Muhammadiyah 8 Surakarta. The aim of the research is: to describe the using of Al-Husna method to increase the quality in reading the holy Qur'ān in Recognizing Al- Qur'ān r gram of SMP Muhammadiyah 8 Surakarta. The location of the research is SMP Muhammadiyah 8 Surakarta and students who participate the extracurricular of Recognizing Al- Qur'ān Program as the object of the research. This isaction research is a qualitative research. The set of data are collected by interview, observation and documentation. The data then, analyzed by inductive method. Based on the analysis of data, it can be concluded that the way of using Al-Husna method in SMP Muhammadiyah 8 Surakarta is by dividing the students into two groups of male and female students accompanied by a tutor of each group. In learning process, students who have not be enable yet to read the holy Qur'ān ill be separated ith the students who can read the holy Qur'ān. That students who have not been able yet to read the holy Qur'ān ill use the b k f Al-Husna. There are many advantages of using Al-Husna method, among them is the students can read faster they only need two semesters. On the other hand, this method also can be used by all of the ages ranging from toddlers to elderly men. The book of Al-Husna is arranged systematically and applicative.